2010
DOI: 10.1088/1367-2630/12/3/035013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of strain and stacking faults in single nanowires using Bragg coherent diffraction imaging

Abstract: Coherent diffraction imaging (CDI) on Bragg reflections is a promising technique for the study of three-dimensional (3D) composition and strain fields in nanostructures, which can be recovered directly from the coherent diffraction data recorded on single objects. In this article we report results obtained for single homogeneous and heterogeneous nanowires with a diameter smaller than 100 nm, for which we used CDI to retrieve information about deformation and faults existing in these wires. The article also di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 57 publications
3
70
0
Order By: Relevance
“…14,15) Other III-V semiconductors, such as GaP and GaAs, are apparently not as close to being unstable as nanowires in the cubic phase; nevertheless, they show a strong trend towards hexagonal stacking along their cubic 111 crystal directions by the introduction of frequent stacking faults. 16) One very interesting example is Zn-doped InP nanowires which show periodic arrays of stacking faults intimately linked to the cross-sectional shape of the wires. 14) Along the wire, the shape evolves from a left-pointing triangle to a right-pointing triangle, then switches direction by the introduction of a stacking fault which reverses the trend in the next half-period.…”
Section: Phase Diagramsmentioning
confidence: 99%
“…14,15) Other III-V semiconductors, such as GaP and GaAs, are apparently not as close to being unstable as nanowires in the cubic phase; nevertheless, they show a strong trend towards hexagonal stacking along their cubic 111 crystal directions by the introduction of frequent stacking faults. 16) One very interesting example is Zn-doped InP nanowires which show periodic arrays of stacking faults intimately linked to the cross-sectional shape of the wires. 14) Along the wire, the shape evolves from a left-pointing triangle to a right-pointing triangle, then switches direction by the introduction of a stacking fault which reverses the trend in the next half-period.…”
Section: Phase Diagramsmentioning
confidence: 99%
“…The nanowires are assumed to be completely relaxed, based on the very short distance for the relaxation of strain in InP/InSb nanowires. 16 Complementary measurements of the 224 reflection were performed to determine the degree of relaxation and composition of the thin InAsSb epilayer. In Fig.…”
Section: Enhanced Sb Incorporation In Inassb Nanowires Grown By Metalmentioning
confidence: 99%
“…We have found that errors due to single precision floating point calculations were not significant in practice: indeed, most of the time structural models for which this type of computation is used are not ideal (see examples of simulated calculations using our code in Tardif et al (2010) and Favre-Nicolin et al (2010)) and therefore do not present a very large dynamic range (larger than 8 orders of magnitude).…”
Section: Figurementioning
confidence: 97%